Effect of BRCA Mutations on Metastatic Relapse and Cause-specific Survival After Radical Treatment for Localised Prostate Cancer - KENNEDY, MICHAEL (My University, 2015)
Background: Germline BRCA mutations are associated with worse prostate cancer (PCa) outcomes; however, the most appropriate management for mutation carriers has not yet been investigated. Objective: To evaluate the response of BRCA carriers to conventional treatments for localised PCa by analysing metastasis-free survival (MFS) and cause-specific survival (CSS) following radical prostatectomy (RP) or external-beam radiation therapy (RT). Design, setting, and participants: Tumour features and outcomes of 1302 patients with local/locally advanced PCa (including 67 BRCA mutation carriers) were analysed. RP was undergone by 535 patients (35 BRCA); 767 received RT (32 BRCA). Median follow-up was 64 mo. Outcome measurements and statistical analysis: Median survival and 3-, 5-, and 10-yr survival rates were estimated using the Kaplan-Meier method. Generated survival curves were compared using the log-rank test. Cox regression analyses were used to assess the prognostic value of BRCA mutations. Results and limitations: A total of 67 BRCA carriers and 1235 noncarriers were included. At 3, 5, and 10 yr after treatment, 97%, 94%, and 84% of noncarriers and 90%, 72%, and 50% of carriers were free from metastasis ( p < 0.001). The 3-, 5- and 10-yr CSS rates were significantly better in the noncarrier cohort (99%, 97%, and 85%, respectively) than in ...
IN_PRESS
Keywords: BRCA carriers; BRCA carriers